2017
DOI: 10.2146/ajhp170113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of automatic infectious diseases consultation on the management of fungemia at a large academic medical center

Abstract: While automatic ID consultation for inpatients with fungemia did not affect the time to administration of appropriate therapy, improvement was observed for several process indicators, including rates of appropriate antifungal therapy selection, time to removal of CVCs, and performance of ophthalmologic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Regarding this aspect, the current study is the first demonstrating how the systematic implementation of a candidemia bundle can be associated with decreased all-cause mortality. Although previous studies showed that infectious disease consultation was associated with better management and patient outcome [11][12][13], we surprisingly found that 89.2% of the patients in the pre-intervention period were visited by an infectious disease specialist. We believe that using a structured ''checklist'' for It is important to mention that other reasons could explain the better evolution of patients treated according to our candidemia bundle.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Regarding this aspect, the current study is the first demonstrating how the systematic implementation of a candidemia bundle can be associated with decreased all-cause mortality. Although previous studies showed that infectious disease consultation was associated with better management and patient outcome [11][12][13], we surprisingly found that 89.2% of the patients in the pre-intervention period were visited by an infectious disease specialist. We believe that using a structured ''checklist'' for It is important to mention that other reasons could explain the better evolution of patients treated according to our candidemia bundle.…”
Section: Discussioncontrasting
confidence: 80%
“…Prompt diagnosis, early administration of appropriate antifungal therapy and adequate source control of infection have been shown to be key factors that improve the prognosis of patients with candidemia [6][7][8][9][10]. Infectious disease (ID) consultations providing diagnostic and therapeutic bedside recommendations as a part of antifungal stewardship programs (ASP) have also been demonstrated to be associated with a better prognosis for candidemic patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In addition to liver cirrhosis, hematological tumor, coinfection and immune diseases, the time from admission to the initiation of antifungal therapy was related to the prolongation of hospitalization. The mean hospital LOS of 14.0 (10.0, 20.0) days was similar to those ranging from 14 days to 16 days in one studies 28 and significantly lower than those ranging from 32.4 to 36 days in other studies. 29,30 It may be that patients in the former hospital were discharged after they had achieved the discharge standard and continued to take the medicine at home until a sufficient course of treatment was achieved.…”
Section: Discussionsupporting
confidence: 76%
“…Automated ID consultations can improve fungal-related clinical issues but may not impact the time to appropriate antifungal therapy. 28 Medical experts unanimously agreed that microscopy and culture were the basic diagnostic tests for fungal infection at present, 31,32 and this study suggested that the consultations by superior physicians should be simple and timely so that patients can receive antifungal treatment as soon as possible to reduce hospital stays and medical expenses.…”
Section: Discussionmentioning
confidence: 86%
“…Our institution is a tertiary-care, academic medical center employing mandatory consultation after identification of a positive blood culture for yeast, the primary team is required to place an infectious diseases consult to aid in management of invasive candidiasis. Such consultation has been shown previously at our institution to improve adherence to quality of care indicators for such infections 11…”
Section: Discussionmentioning
confidence: 78%